N-Palmitoylethanolamine Maintains Local Lipid Homeostasis to Relieve Sleep Deprivation–Induced Dry Eye Syndrome - Chen, Qi; Ji, Chunyan; Zheng, Ruihe; Yang, Longhe; Ren, Jie; Li, Yitian; Han, Yun; Zhou, Pan; Liu, Zuguo; Qiu, Yan (Frontiers in Pharmacology, 2020)
Sleep loss is a key factor associated with dry eye. Use of a “stick over water” mouse model revealed that sleep deprivation induces accumulation of lipids, hypertrophy, and dysfunction of the lacrimal gland. These changes result in decreased tear production and dry eye clinical signs. The specific pathophysiological mechanisms that contribute to dry eye remain unclear. In this study, we found that sleep deprivation decreased endogenous lipid palmitoylethanolamide (PEA) expression in the lacrimal gland. The reduced expression was mainly attributed to the decreased expression of N-acylated phosphatidylethanolamine–phospholipase D, the synthetic enzyme of PEA. Exogenous PEA treatment restored local lipid metabolism homeostasis in the lacrimal gland. This change was accompanied by reduced lipid deposition, maintenance of the endoplasmic reticulum and mitochondrial morphology, and improved acinar cell secretory function. PEA treatment also prevented damage to corneal barrier function and improved the dry eye clinical signs caused by sleep deprivation. The nuclear receptor peroxisome proliferator-activated receptor-α (PPAR-α) was found to mediate the PEA-associated improvements. We describe here for the first time that PEA is involved in sleep deprivation–induced lacrimal gland pathogenesis and dry eye development. PEA and its metabolizing enzymes may serve as adjunctive therapeutic targets for treatment of dry eye.